PERAN PENYIDIK OTORITAS JASA KEUANGAN DALAM MENJAGA STABILITAS SEKTOR JASA KEUANGAN INDONESIA - Kusumaningsih, Rila (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
Investigators from the Financial Services Authority (OJK) play a crucial role in the oversight and regulation of the financial sector in Indonesia. They are responsible for investigating legal violations, fraud, and mismanagement that may occur in financial institutions. OJK investigators conduct audits and examinations to ensure compliance with existing regulations. If violations are found, they can collaborate with other law enforcement agencies to follow up and take appropriate legal actions. Additionally, OJK investigators also contribute by providing recommendations to financial institutions to improve their practices. Through their roles, OJK investigators contribute to maintaining the stability and integrity of Indonesia's financial sector while protecting customers and investors.